The Relationship of Hypermenorrhea with the Incidence of Anemia in Young Women at An Nikmah Islamic Boarding School, Sagulung - Tinta Julianawati; Siti Nur Lela (UIMA Press, 2021)
Background: Anemia in adolescents can have an impact on decreasing work productivity or academic ability at school, because there is no passion for learning and a decrease in learning concentration. To overcome the problem of anemia in young women, IEC (Communication, Information and Education) activities are carried out, namely promotions or campaigns about anemia to the public wide area, supported by group counseling and counseling activities that are shown directly to young women. Objectives: The purpose of this research was to analyze the correlation between hypermenorrhea and the incidence of anemia in adolescent girls. Methods: The research design was Analytic survey. The whole of the girl in 10-19 years old who get hipermenorea in An Nikmah Islamic Islamic Boarding School, 57 populations with 50 respondents were taken by simple random sampling technique.The variable was hipermenorea and the parameter was anemia. The data analyzing used Chi Square Test, is ρ value 0,000, if 0,000<0,005 (H0 is rejected and H1 accepted). Results: From the results we get that there is a correlation between the incidence of hypermenorrhoea with anemia in An Nikmah Islamic Boarding School. Conclusion: Conclusion is many bleedings occurs during menstrual process can cause anemia in young women.